The Role of the State Administrative Court in Realizing Good Governance - Surya, Ida (International Journal of Scientific Research and Management (IJSRM), 2023)
Indonesia is a state of Law based on Pancasila and the 1945 Constitution aimed at realizing a prosperous, safe, peaceful and peaceful life for the State and nation and ensuring the equal position of citizens in Law, providing the maintenance of harmonious, balanced, and cooperative relations between State bodies or officials and citizens, in an effort by the Government to organize people's lives to achieve the State's goal of protecting the entire Indonesian nation. All to promote the general welfare, educate the nation's life and all Indonesian bloodshed, promote the general welfare, educate the nation's energy, and participate in implementing world order based on independence, lasting peace, and social justice. The administration of Government should create a condition that leads to the goal that citizens can feel and enjoy the atmosphere and climate of order and legal certainty that is just. In its implementation, there are often conflicts of interest, disputes, and disputes between the State Administration Agency or Officer and citizens that harm or hinder the performance of the Government. The argument is resolved through the State Administrative Court, which must be able to uphold justice, truth, order, and legal certainty so as to provide protection to the community, especially in the relationship between the State Administrative Agency or Officer and the community because the position of the Government is stronger than the people, legal protection of the people must be carried out by a free and independent judicial process. The State Administrative Court resolves the dispute by Law Number 9 of 2004. The State Administrative Court is one of the independent free state judiciary bodies without the influence of other powers, adhering to Pancasila and the 1945 Constitution of the Republic of Indonesia and applicable laws and regulations to juridically control government actions that violate administrative provisions.